New Wave in Mobile Commerce Adoption via Mobile Applications in Malaysian Market: Investigating the Relationship Between Consumer Acceptance, Trust, and Self Efficacy - Singh, Satwinderjit; Zolkepli, Izzal Asnira; Wen Kit, Cheah (International Journal of Interactive Mobile Technologies (iJIM), 2018)
Given the prevalence of online technology nowadays, mobile commerce continues to attract considerable attention for marketing research. However, studies on the factors that impact mobile commerce adoption via mobile applications are still limited. Moreover, there is minimal study that investigates the importance of attitudes towards mobile commerce as antecedents of mobile commerce adoption using Technology Acceptance Model (TAM), especially in the Malaysian market. These factors are crucial since the population of online users are massive and their influence is forming the untapped potential for marketers. By knowing the factors that drive the use of mobile commerce, this study seeks to facilitate marketers on how to use the findings and intensify the growth of online business in Malaysia. This quantitative study is cross-sectional in nature with 160 samples. Results showed that out of six hypotheses, five hypotheses were supported. The findings shed lights on the relevance of TAM in reasoning the adoption of mobile commerce via mobile applications. Also, this study provides insightful implications for marketers to understand consumer behaviour and strengthen the mobile commerce market.